Molecular dynamics study of damage nearby silicon surface bombarded by energetic carbon ions - Liang, Guoying; Zhong, Haowen; Zhang, Shijian; Xu, Mofei; Kuang, Shicheng; Ren, Jianhui; Zhang, Nan; Yan, Sha; Yu, Xiao; Remnev, Gennady Efimovich; Le, Xiaoyun (Surface & coatings technology, 2020)
This paper investigates damage generation and evolution nearby silicon surface bombarded by energetic carbon ions by using molecular dynamics simulations. We experimentally measured elementary composition in defect regions based on energy dispersive spectrometer analysis. Using molecular dynamics simulations, point defects generation and evolution in monocrystalline silicon were illustrated. The percentage of carbon in defect regions is significantly more than that in non-irradiated regions of monocrystalline silicon. Point defects rapidly generate at the beginning of collision cascades between projective carbon ions and silicon atoms. The radial straggling and penetration along the depth direction are respectively dominant when projective ions with different kinetic energies implant into silicon target. These results can be used to better understand the interaction between projective energetic ions and target. •Point defects rapidly generate at the beginning of cascade collision.•Carbon in defect regions is significantly more than in non-irradiated regions.•The radial straggling and penetration along the depth direction are respectively dominant.